2019
DOI: 10.1073/pnas.1911028117
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from equilibrium statistical physics regarding the assembly of protein complexes

Abstract: Cellular functions are established through biological evolution, but are constrained by the laws of physics. For instance, the physics of protein folding limits the lengths of cellular polypeptide chains. Consequently, many cellular functions are carried out not by long, isolated proteins, but rather by multiprotein complexes. Protein complexes themselves do not escape physical constraints, one of the most important being the difficulty of assembling reliably in the presence of cellular noise. In order to lay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 44 publications
(53 reference statements)
1
52
0
Order By: Relevance
“…Most of the proteins found in more than one complex are core subunits of complexes of which many different variants exist, such as cyclin-dependent kinases or ubiquitin ligases. In a recent analysis of datasets from several yeast interactome datasets it was demonstrated that this long right-hand tail of a few proteins occurring in many complexes is almost always significantly different from a random distribution (37). The random distribution estimates that proteins should be found in a maximum of 6-9 complexes while in the real data some proteins occur in >20 complexes, matching our observations.…”
Section: Multifunctionalitysupporting
confidence: 86%
See 2 more Smart Citations
“…Most of the proteins found in more than one complex are core subunits of complexes of which many different variants exist, such as cyclin-dependent kinases or ubiquitin ligases. In a recent analysis of datasets from several yeast interactome datasets it was demonstrated that this long right-hand tail of a few proteins occurring in many complexes is almost always significantly different from a random distribution (37). The random distribution estimates that proteins should be found in a maximum of 6-9 complexes while in the real data some proteins occur in >20 complexes, matching our observations.…”
Section: Multifunctionalitysupporting
confidence: 86%
“…To date, the Complex Portal yeast complexome has been used to validate complexes in several large-scale studies (37,(39)(40)(41)(42) As we move to complete more complexomes, for example that of Escherichia coli, and continually improve our coverage of the human and mouse complexes, it will also be possible to improve our understanding of the evolution of these assemblies (50), and from there how the regulation of cellular processes has developed as organisms evolve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A check against the GO annotation of these proteins showed that many are catalytic core subunits of complexes such as cyclin-dependent kinases or ubiquitin ligases. In a recent analysis of datasets from several yeast interactome datasets, it was demonstrated that this long right-hand tail of a few proteins occurring in many complexes is almost always significantly different from a random distribution ( 38 ). The random distribution estimates that proteins should be found in a maximum of 6–9 complexes while in the real data some proteins occur in >20 complexes, matching our observations.…”
Section: Resultsmentioning
confidence: 99%
“…Without templating of far-from-equilibrium ensembles it would be impossible to achieve the chemical complexity of biology. For example, there simply cannot be enough information stored in the interactions between 20 basic building blocks (the standard amino acids) to code for the selective assembly of tens of thousands of specific proteins -and only those proteins -from a mixture of only these amino acids 16 . Far-from-equilibrium templating solves this problem by providing a reusable mechanism to assemble an arbitrary polypeptide chain.…”
mentioning
confidence: 99%